Analysis of Rainfall Characteristicsfor Flood Estimation in Way Awi Watershed - Dyah I. Kusumastuti; D. Jokowinarno; C.H. Van Rafii; F. Yuniarti (Civil Engineering Dimension, 2016)
This study investigates rainfall intensity distribution in Way Awi watershed located in Bandar Lampung, and how their impacts on flood peak and flood hydrographs. Hourly rainfall data is examined to obtain design rainfall intensity and rainfall intensity distribution at rainfall duration from three to eight hours. Rainfall-runoff model, i.e. Rational method is used to calculate flood peak while unit hydrograph method is used to develop flood hydrograph. This study shows that in Way Awi watershed 88.3% to 96.4% of 24-hour rain occurs in three to eight hour durations. In addition, rainfall with three hour duration generates the highest flood peak, followed by four hour duration rainfall. When rainfall duration and design rainfall intensity are the same but rainfall intensity distribution is different, generated flood hydrograph may have different flood peak magnitude and timing. Result of this study is useful for flood analysis and mitigation in Way Awi watershed.